أثر العلوم اللغوية والإنسانية والفلسفية في آليات التأويل الغربي - بختي, البشير (جامعة الوادي - university of Eloued, 2022)
وظف التأويل الغربي كلاًّ من العلوم اللغوية والإنسانية والفلسفية في تكوين آلياته وإجراءاته القرائية. ومنذ القديم، اعتمد التأويل اللغوي اللاهوتي - في قراءته للكتب السماوية "التوراة والإنجيل والقرآن الكريم"- على علوم اللغة "كالنحو والصرف والمعجم"، و كان يهدف - في البداية - إلى البحث عن المعنى الحقيقي للنصوص الدينية. وقد استفادت التأويلية الرومانسية لـ"شلاير ماخر" من العلوم اللغوية، بالإضافة إلى توظيفها لعلم النفس. وألح "فيلهلم دلتاي" في تأويليته على الاستعانة بالعلوم الإنسانية، أو كما سماها علوم الروح، واستبعد العلوم الطبيعية لأنها لا تصلح في مقاربة النصوص الإنسانية. بينما نجد تأويلية "مارتن هيدجير" وقد نشأت في فلسفة الوجود، وصارت تهتم بفهم الوجود من خلال اللغة بدل البحث عن المعنى. ويسعى البحث إلى التعريف بالتأويليات الغربية الحديثة التي تقاطعت مع العلوم اللغوية والإنسانية والفلسفية، وإلى إظهار أثرها في تشكيل الآليات التأويلية الحديثة. وذلك بعد أن حل عصر التنوير الذي بفضله ازدهرت الهرمينوطيقا كما استفادت من تشكل العلوم الإنسانية بخاصة علم النفس. وسنتناول كلاًّ من التأويلية الرومانسية لشلاير ماخر وتأويلية دلتاي وتأويلية مارتن هيدجر، ونبحث عن العلوم اللغوية والإنسانية والفلسفية التي تقاطعت معها. Western hermeneutics has employed the linguistic, human and philosophical sciences in forming its reading mechanisms and procedures. Since antiquity, the linguistic and theological interpretation of the divine books (the Torah, the Gospel and the Noble Koran) relied on the sciences of language including grammar, morphology and lexicon to identify initially the real meaning of religious texts. In fact, Schleiermacher's romantic hermeneutics used the linguistic sciences, as well as psychology while that of Wilhelm Dilthey was based on the human sciences (the spiritual sciences according to him) and excluding the natural sciences because they are not useful for studying human texts. As for Martin Heidegger, he based his hermeneutical approach on existential philosophy focused on understanding existence through language rather than seeking the meaning. This research aims to introduce the approaches of modern western hermeneutics intersected with linguistic, human and philosophical sciences, and to reveal their impact on the formation of modern hermeneutic mechanisms especially after the beginning of the Enlightenment era when hermeneutics has been flourished and benefiting from the human sciences, particularly psychology. We study the hermeneutics in Schleiermacher, Dilthey and Martin Heidegger, and we identify the linguistic, human and philosophical sciences associated with this discipline.
مقال
Keywords: علوم اللغة؛ علم النفس؛ التاريخ؛ الفلسفة؛ الهرمينوطيقا